2014
DOI: 10.1099/mic.0.082180-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic impact of an NADH-producing glucose-6-phosphate dehydrogenase in Escherichia coli

Abstract: In Escherichia coli, the oxidative branch of the pentose phosphate pathway (oxPPP) is one of the major sources of NADPH when glucose is the sole carbon nutrient. However, unbalanced NADPH production causes growth impairment as observed in a strain lacking phosphoglucoisomerase (Dpgi). In this work, we studied the metabolic response of this bacterium to the replacement of its glucose-6-phosphate dehydrogenase (G6PDH) by an NADH-producing variant. The homologous enzyme from Leuconostoc mesenteroides was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 56 publications
3
22
2
Order By: Relevance
“…It has been shown previously that disrupting the gnd gene resulted in non appreciable changes to growth rate, but induces major changes in fluxes through the PPP and TCA cycle [1][2][3] . Similar observations have also been made of zwf mutants 4,5 , which demonstrate that metabolic networks can rapidly adjust enzyme level and flux without an appreciable cost to growth rate.…”
Section: Introductionsupporting
confidence: 72%
“…It has been shown previously that disrupting the gnd gene resulted in non appreciable changes to growth rate, but induces major changes in fluxes through the PPP and TCA cycle [1][2][3] . Similar observations have also been made of zwf mutants 4,5 , which demonstrate that metabolic networks can rapidly adjust enzyme level and flux without an appreciable cost to growth rate.…”
Section: Introductionsupporting
confidence: 72%
“…Because the genes gnd and zwf-2 are in the same operon, the activity of 6phosphogluconate dehydrogenase (GND) could indirectly indicate the expression of the protein encoded by zwf-2, annotated as another G6PDH. 13 C-labeling experiments had shown that the oxidative branch of the pentose-phosphate pathway is operative in P. putida KT2440 when glucose is the sole carbon source [2], so we decided to measure the activity of GND in the crude cellular extracts ( Table 3). The registered GND activities together with the biased estimations of E (Fig.…”
Section: Pputg6pdh-1 Is Not the Only Form Of G6pdh Expressed During Tmentioning
confidence: 99%
“…However, this analysis involved considerably shorter simulations (0.5 ps), not intended to evaluate the stability of protein-ligand binding. In addition, we previously reported MD simulations of the dual Lm G6PDH with NAD + and NADP + , based on its crystallographic complexes [ 11 ]. In this enzyme, the R46 residue is homologous to R50 of Ec G6PDH ( Fig 6 ) and has been shown to perform an equivalent function in the interaction with the 2’-phosphate of NADP + [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…coli enzyme and is important for interacting with the 2’-phosphate and the ribose-3’-hydroxyl group of NADP + . Interestingly, in opposition to Ec G6PDH, the simulations of the Lm G6PDH-NAD + complex showed that the ribose-adenine region was stable in its pocket, mainly because of stable hydrogen bonding with the main chain atoms of T14 and R46, together with a stabilizing interaction with the side chains of Q47 and T14 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation